A Two‐Electron Silver Superatom Isolated from Thermally Induced Internal Redox Reaction of A Silver(I) Hydride. (16th April 2021) - Zhong, Yu‐Jie; Liao, Jian‐Hong; Chiu, Tzu‐Hao; Kahlal, Samia; Lin, Che‐Jen; Saillard, Jean‐Yves; Liu, C. W.
Abstract: Rational syntheses under controllable reducing conditions in the preparation of superatoms with cluster electron number not exceeding two are challenging. Herein a dithiolate‐stabilized two‐electron silver nanocluster, Ag10 {S2 P(O i Pr)2 }8 (1 ), is isolated via a self‐redox reaction of Ag7 (H){S2 P(O i Pr)2 }6 without adding extra reducing agents. The metal framework of Ag7, a bicapped trigonal bipyramid, is highly correlated to that of Ag10, suggesting Ag7 (H){S2 P(O i Pr)2 }6 acts as both reducing agent and template in cluster growth. 1 is highly fluorescent at ambient temperature and TD‐DFT calculations indicate that the emission is of 1Px →1S nature. Abstract : A self‐redox reaction of Ag7 (H){S2 P(O i Pr)2 }6 leads to the formation of a highly emissive, two‐electron Ag nanocluster, Ag10 {S2 P(O i Pr)2 }8, without adding extra reducing agents. The metal framework of Ag7, a bicapped trigonal bipyramid, is highly correlated to that of Ag10, suggesting Ag7 (H){S2 P(O i Pr)2 }6 acts as both reducing agent and template in cluster growth.